WORK AND JUSTICE WITHOUT MORAL CONTENT IN HESIOD’S WORKS AND DAYS - Refik Guremen (Felsefe Dünyası)
According to Michael Gagarin, Hesiod’s notion of dikê is not a moral notion, and it has to be disassociated from the moral connotations that it will start to assume later in the fifth century. For Gagarin, an ad hoc settlement of particular disputes in city courts is all there is to Hesiodic dikê. This article objects to this interpretation of Hesiod and claims that Hesiod is working with a more substantial idea of dikê in his Works and Days. According to my reading, however, Hesiod’s more substantial notion of dikê still does not have moral content. I provide my reasons for this latter claim by showing that “work”, for Hesiod, does not have a moral significance, either.